Transfer sheet, method for producing transfer sheet, method for producing exterior member, and exterior member

The transfer sheet addresses adhesion and scratch resistance issues by using specific resin compositions with controlled indentation hardness, ensuring durable performance in exterior applications.

JP7613492B2Active Publication Date: 2025-01-15DAI NIPPON PRINTING CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023030228
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-02-28
Publication Date
2025-01-15
Estimated Expiration
2043-02-28

AI Technical Summary

Technical Problem

Transfer sheets used for decorating exterior components face issues with insufficient adhesion between protective layers, particularly in harsh environments, and lack scratch resistance and weather-resistant adhesion.

Method used

A transfer sheet design with a first protective layer containing a cured product of a first curable resin composition and weathering agent, and a second protective layer with a cured product of a second curable resin composition, both incorporating (meth)acrylic and urethane components, with specific indentation hardness ranges to ensure good adhesion and scratch resistance.

Benefits of technology

The transfer sheet achieves excellent scratch resistance and weather-resistant adhesion between protective layers, suitable for exterior components, maintaining properties even in harsh conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613492000002
    Figure 0007613492000002
  • Figure 0007613492000003
    Figure 0007613492000003
  • Figure 0007613492000004
    Figure 0007613492000004
Patent Text Reader

Abstract

To provide a transfer sheet which enables transfer of a transfer layer that is excellent in scratch resistance and has good weather-resistant adhesion between a first protective layer and a second protective layer.SOLUTION: A transfer sheet 10 has a release film 1, and a transfer layer arranged on one surface of the release film, wherein the transfer layer has a first protective layer 2 and a second protective layer 3 in this order from the release film side, the first protective layer contains a cured product of a first curable resin composition and a weather-resistant agent, the second protective layer contains a cured product of a second curable resin composition and a weather-resistant agent, each of the cured product of the first curable resin composition and the cured product of the second curable resin composition contains a (meth)acrylic component and an urethane component, when a cross sectional sample piece of the transfer sheet is manufactured using a resin embedding method and a microtome, indentation hardness in the cross section of the first protective layer is 150 MPa or more and 300 MPa or less, and indentation hardness in the cross section of the second protective layer is 2 MPa or more and 50 MPa or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a transfer sheet, a method for producing a transfer sheet, a method for producing an exterior member, and an exterior member. [Background technology]

[0002] It is known to decorate a base such as a metal member or a resin member by transferring a transfer layer (a layer transferred from the transfer sheet) of a transfer sheet to the base. For example, Patent Document 1 discloses a design transfer sheet including a release layer and a design transfer layer removably attached to the release layer, the design transfer layer including, from the release layer side, a first surface layer capable of being heat-bonded and a second surface layer capable of being heat-bonded, in this order. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2016-120643 A Summary of the Invention [Problem to be solved by the invention]

[0004] The transfer sheet has, for example, a release film, a first protective layer, and a second protective layer in this order in the thickness direction. In such a transfer sheet, the adhesion of the first protective layer and the second protective layer is likely to be insufficient. The first protective layer is typically produced by curing a composition for forming the first protective layer on a release film. Since the second protective layer is formed on the cured first protective layer, the adhesion of the first protective layer and the second protective layer is likely to be insufficient. In addition, since exterior members (outdoor members) are exposed to harsh environments, the first protective layer and the second protective layer constituting the transfer layer in the transfer sheet used in the manufacture of exterior members are required to have not only good initial adhesion but also good weather-resistant adhesion. In addition, the transfer sheet is required to have a scratch-resistant surface of the transfer layer transferred to the substrate.

[0005] The present disclosure has been made in consideration of the above-mentioned situation, and has as its main object to provide a transfer sheet capable of transferring a transfer layer that has excellent scratch resistance and good weather-resistant adhesion to a first protective layer and a second protective layer. [Means for solving the problem]

[0006] The present disclosure provides a transfer sheet used in the manufacture of an exterior member, the transfer sheet having a release film and a transfer layer disposed on one side of the release film, the transfer layer having a first protective layer and a second protective layer in this order in the thickness direction from the release film side, the first protective layer containing a cured product of a first curable resin composition and a weathering agent, the second protective layer containing a cured product of a second curable resin composition and a weathering agent, the cured product of the first curable resin composition and the cured product of the second curable resin composition each containing a (meth)acrylic component and a urethane component, and when a cross-sectional sample piece of the transfer sheet is prepared using a resin embedding method and a microtome, the indentation hardness of the cross section of the first protective layer is 150 MPa or more and 300 MPa or less, and the indentation hardness of the cross section of the second protective layer is 2 MPa or more and 50 MPa or less.

[0007] The present disclosure also provides a method for producing the above-mentioned transfer sheet, comprising: a first protective layer formation step of applying a first composition containing the first curable resin composition and the weather resistance agent to a surface of the release film, curing the composition to form the first protective layer; and a second protective layer formation step of applying a second composition containing the second curable resin composition and the weather resistance agent to a surface of the first protective layer opposite the release film, curing the composition to form the second protective layer.

[0008] The present disclosure provides a method for manufacturing an exterior member, the method including a preparation step of preparing the above-mentioned transfer sheet, and a bonding step of opposing the surface of the transfer sheet facing the second protective layer to a substrate and bonding the two together.

[0009] The present disclosure provides an exterior member having a first protective layer, a second protective layer, an adhesive layer, and a base, in this order in the thickness direction, wherein the first protective layer contains a cured product of a first curable resin composition and a weathering agent, the second protective layer contains a cured product of a second curable resin composition and a weathering agent, and the cured product of the first curable resin composition and the cured product of the second curable resin composition each contain a (meth)acrylic component and a urethane component, and when a cross-sectional sample piece of the exterior member is prepared using a resin embedding method and a microtome, the indentation hardness of the cross section of the first protective layer is 150 MPa or more and 300 MPa or less, and the indentation hardness of the cross section of the second protective layer is 2 MPa or more and 50 MPa or less. Effect of the Invention

[0010] The present disclosure has an effect of providing a transfer sheet capable of transferring a transfer layer having excellent scratch resistance and good weather-resistant adhesion to a first protective layer and a second protective layer. [Brief description of the drawings]

[0011] [Figure 1] 1 is a schematic cross-sectional view illustrating a transfer sheet according to the present disclosure. [Diagram 2] 1A to 1C are schematic cross-sectional views illustrating a method for producing a transfer sheet in the present disclosure. [Diagram 3] 1A to 1C are schematic cross-sectional views illustrating a method for manufacturing an exterior member in the present disclosure. [Figure 4] 1 is a schematic cross-sectional view showing an example of an exterior member according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The following describes the embodiments with reference to the drawings. However, the present disclosure can be implemented in many different forms and should not be limited to the description of the embodiments exemplified below. In addition, the drawings may show the width, thickness, and shape of each part in a schematic manner compared to the actual form in order to make the description clearer, but this is merely an example and should not be interpreted as being limiting.

[0013] In this specification, when describing a mode in which another component is disposed on a certain component, the term "above" or "below" includes both cases in which another component is disposed directly above or below the certain component so as to be in contact with the component, and cases in which another component is disposed above or below the certain component with another component interposed therebetween, unless otherwise specified. In addition, in this specification, when describing a mode in which another component is disposed on the surface of a certain component, the term "on the surface" includes both cases in which another component is disposed directly above or below the certain component so as to be in contact with the component, and cases in which another component is disposed above or below the certain component with another component interposed therebetween, unless otherwise specified.

[0014] The transfer sheet, the method for producing the transfer sheet, the method for producing the exterior member, and the exterior member according to the present disclosure will be described in detail below.

[0015] A. Transfer sheet 1(a) is a schematic cross-sectional view illustrating a transfer sheet in the present disclosure. As shown in FIG. 1(a), a transfer sheet 10 has a release film 1 and a transfer layer X arranged on one surface of the release film 1. The transfer layer X is a first protective layer 2 and a second protective layer 3 from the release film 1 side in a thickness direction D. T In the above, the transfer sheet 10 has the above layers in this order. As shown in FIG. 1(b), the transfer sheet 10 may have an adhesive layer 4 on the surface of the second protective layer 3 opposite the first protective layer 2. As shown in FIG. 1(c), the transfer sheet 10 may have a design layer 5 on the surface of the second protective layer 3 opposite the first protective layer 2. As shown in FIG. 1(d), the transfer sheet 10 may have an adhesive layer 4 on the surface of the design layer 5 opposite the second protective layer 3.

[0016] In the transfer sheet of the present disclosure, the first protective layer 2 contains a cured product of a predetermined first curable resin composition and a weathering agent, and the indentation hardness of a cross section of a cross-sectional sample piece of the transfer sheet produced by a predetermined method is within a predetermined range. Furthermore, the second protective layer 3 contains a cured product of a predetermined second curable resin composition and a weathering agent, and the indentation hardness of a cross section of a cross-sectional sample piece of the transfer sheet produced by a predetermined method is within a predetermined range. According to the present disclosure, a transfer sheet for exterior members having good weather-resistant adhesion and scratch resistance is obtained.

[0017] As described above, in the transfer sheet, the adhesion of the first protective layer and the second protective layer is likely to be insufficient. Here, in the case of a decorative sheet, a design layer is usually formed on a base layer, then a second protective layer is formed on the design layer, and then the first protective layer is formed on the second protective layer. The first protective layer is typically produced by curing a composition for forming the first protective layer formed on the second protective layer, so that the adhesion of the first protective layer and the second protective layer is good. In contrast, in the case of a transfer sheet, the first protective layer is typically formed on a release film, then a second protective layer is formed on the first protective layer, and then a design layer is formed on the second protective layer. The first protective layer is typically produced by curing a composition for forming the first protective layer on a release film. The second protective layer is formed on the cured first protective layer, so that the adhesion of the first protective layer and the second protective layer is likely to be insufficient.

[0018] Since the first protective layer is required to have good scratch resistance, it is preferable that the flexibility of the first protective layer is low. The inventors of the present application have also found that the second protective layer needs to have a certain degree of flexibility in order to adhere to the hardened first protective layer (initial adhesion and weather-resistant adhesion). Furthermore, they have found that in an environment where temperature changes such as temperature differences between day and night and seasonal temperature differences occur repeatedly, the first protective layer cannot follow the second protective layer, and weather-resistant adhesion may deteriorate.

[0019] The present inventors have found that the indentation hardness obtained by measuring a cross-sectional sample piece of a transfer sheet prepared using a resin embedding method and a microtome can evaluate the flexibility of a layer more accurately than the indentation hardness obtained by measuring a cross-sectional sample piece prepared by mechanical polishing, etc. The present inventors have found that when a cross-sectional sample piece of the transfer sheet is prepared using a resin embedding method and a microtome, the indentation hardness of the cross section of the first protective layer is within a predetermined range, and the indentation hardness of the cross section of the second protective layer is within a predetermined range, resulting in a transfer sheet capable of transferring a transfer layer having excellent scratch resistance and good weather-resistant adhesion of the first protective layer and the second protective layer.

[0020] In addition, exterior members (outdoor members) are required to have higher weather resistance than interior members (indoor members). For example, when manufacturing an exterior member using a decorative sheet, a transparent resin layer may be provided on the decorative sheet for the purpose of improving strength. In this case, since the transparent resin layer is a relatively thick layer, for example, high weather resistance is imparted by adding a sufficient amount of weather resistance agent to the transparent resin layer. In contrast, it is technically difficult to impart high weather resistance to a transfer sheet that does not have a layer corresponding to the transparent resin layer. In the present disclosure, both the first protective layer and the second protective layer usually contain a weather resistance agent. This makes it possible to impart high weather resistance while maintaining the properties required for the first protective layer (for example, surface properties such as scratch resistance and abrasion resistance) and the properties required for the second protective layer (for example, adhesion).

[0021] 1.1st protective layer The transfer sheet in the present disclosure has a first protective layer. The first protective layer contributes to improving the surface properties (e.g., scratch resistance, abrasion resistance, etc.) of the exterior member. The first protective layer and the release film are preferably arranged so as to be in direct contact with each other.

[0022] (1) Indentation hardness In the present disclosure, when a cross-sectional sample piece of a transfer sheet is prepared using a resin embedding method and a microtome, the indentation hardness of the cross-section of the first protective layer is usually 150 MPa or more, may be 180 MPa or more, or may be 190 MPa or more. If the indentation hardness of the cross-section of the first protective layer is low, good scratch resistance and abrasion resistance may not be obtained. On the other hand, the indentation hardness of the cross-section of the first protective layer is usually 300 MPa or less, may be 280 MPa or less, or may be 250 MPa or less. If the indentation hardness of the cross-section of the first protective layer is high, the conformability of the first protective layer to the second protective layer is low, and good weather-resistant adhesion may not be obtained.

[0023] The indentation hardness of the cross section of the first protective layer can be adjusted, for example, by the number of functional groups of the curable resin in the first curable resin composition for producing the first protective layer. For example, by reducing the number of functional groups of the ionizing radiation curable compound, the number of crosslinking points in the cured product of the first curable resin composition can be reduced, resulting in a more flexible structure and a lower indentation hardness.

[0024] The indentation hardness of the cross section of the first protective layer was a value obtained by measuring a cross-sectional sample piece prepared using a resin embedding method and a microtome according to the indentation hardness measuring method described below. (Method of preparing cross-sectional sample pieces for measurement) The transfer sheet is cut to an arbitrary size to prepare a cut sample. The cut sample is embedded in resin (a room temperature curing type epoxy two-part curing resin) and left at room temperature for 24 hours or more to harden, thereby preparing an embedded sample in which the cut sample is embedded in resin (resin embedding method). The embedded sample is cut vertically using a microtome to expose the cross section of the layer to be measured, thereby preparing a cross-sectional sample piece for indentation hardness measurement. Specifically, a cross section is prepared in an environment of -120°C by using an ultramicrotome (Leica EM UC6, manufactured by Leica Microsystems) equipped with a freezing cutting system (Leica EM FC6, manufactured by Leica Microsystems) and a diamond knife, exposing the cross section of the layer to be measured. Compared to a cross section cut in an environment of room temperature, cross-sectional roughness can be suppressed, and a cross section suitable for indentation testing can be obtained. In particular, cross-sectional roughness can be suppressed in the case of soft materials.

[0025] (Method of measuring indentation hardness) In this specification, the "indentation hardness" is measured by the nanoindentation method, which is a method for continuously measuring the load and displacement during the process of pressing an indenter into the surface of a sample and unloading it, and calculating the mechanical quantity from the obtained load-displacement curve.

[0026] Specifically, the indentation hardness in the cross section of the first protective layer is measured by pressing a Berkovich indenter (material: diamond triangular pyramid) perpendicularly into the cut surface of the above-mentioned measurement sample using the following nanoindenter. The measurement device and measurement conditions are as follows. Here, the position where the Berkovich indenter is pressed is preferably approximately the center in the thickness direction of the first protective layer. Approximately the center means that when the thickness of the first protective layer is defined as T [μm], the deviation from the center in the thickness direction of the first protective layer is within ±0.1 T. In addition, when fine particles such as a filler (e.g., silica) are contained in the layer, the Berkovich indenter is pressed into a position that avoids the fine particles.

[0027] Equipment used: Nanoindenter (TI 950 TriboIndenter, manufactured by BRUKER) Indenter used: Berkovich indenter (model number: TI-0039, manufactured by BRUKER) Push-in control method: Displacement control method (no lift operation) Maximum indentation depth: 100nm Push rate: 10nm / sec Loading time: 10 seconds (pushing from 0 to 100 nm) ·Holding time: 5 seconds (100nm constant) Unloading time: 10 seconds (100 nm → return to 0) Number of measurements: 5

[0028] The indentation hardness of the cross section of the first protective layer can be calculated as follows. First, the indentation depth h (nm) corresponding to the indentation load P (N) is continuously measured, and a load-displacement curve is created. The created load-displacement curve is analyzed to determine the maximum indentation load P max (N) is expressed as the projected area A (mm 2 ) is the indentation hardness H IT can be calculated (formula (1) below). H IT =P max / A …(1) Here, A is the contact projected area obtained by correcting the indenter tip shape using a standard sample of fused quartz in a standard manner.

[0029] In this specification, the indentation hardness at the cross section of the first protective layer is the arithmetic average value of five measurements of the same sample, with the position shifted. Each measurement is measured with a shift of 5 μm or more. During the measurement, in order to confirm that the correction of the indenter shape is correctly performed and that there are no problems with the operation and measurement of the device, it is preferable to confirm that the measurement is performed within ±5% of the reference value using fused quartz, which is the standard sample of the device manufacturer. The indentation hardness is measured in an atmosphere with a temperature of 23°C ±5°C and a humidity of 40% to 65%.

[0030] (2) Resin component The first protective layer contains a cured product (crosslinked structure) of the first curable resin composition. The cured product of the first curable resin composition contains a (meth)acrylic component and a urethane component. The (meth)acrylic component refers to an acrylic component or a methacrylic component. The urethane component refers to a urethane bond. The proportion of the cured product of the first curable resin composition is, for example, 70% by mass or more, may be 90% by mass or more, may be 95% by mass or more, or may be 100% by mass, based on the total resin components constituting the first protective layer.

[0031] Examples of the first curable resin composition include an ionizing radiation curable resin composition and a heat curable resin composition. Examples of the ionizing radiation curable resin composition include an electron beam curable resin composition and an ultraviolet ray curable resin composition. Among these, an electron beam curable resin composition is preferred because it does not require a polymerization initiator, has little odor, and is less likely to cause coloring.

[0032] The ionizing radiation curable resin composition is a composition containing a compound having an ionizing radiation curable functional group (hereinafter also referred to as "ionizing radiation curable compound"). The ionizing radiation curable functional group is a group that crosslinks and cures when irradiated with ionizing radiation. The ionizing radiation curable resin composition preferably contains at least a compound having a (meth)acryloyl group. The (meth)acryloyl group refers to an acryloyl group or a methacryloyl group. The ionizing radiation curable resin composition may also contain a compound having a functional group having an ethylenic double bond, such as a vinyl group or an allyl group, in addition to the compound having a (meth)acryloyl group.

[0033] The number of functional groups of the ionizing radiation curable compound is preferably from 2 to 20, more preferably from 2 to 18, and even more preferably from 2 to 15. This is because the indentation hardness of the first protective layer can be easily adjusted to within the above range.

[0034] Ionizing radiation refers to electromagnetic waves or charged particle beams that have an energy quantum capable of polymerizing or crosslinking molecules. Examples of ionizing radiation include electron beams (EB) and ultraviolet rays (UV). Other examples of ionizing radiation include electromagnetic waves such as X-rays and gamma rays, and charged particle beams such as alpha rays and ion beams.

[0035] The ionizing radiation curable resin composition preferably contains at least a urethane (meth)acrylate as an ionizing radiation curable compound. (Meth)acrylate refers to acrylate or methacrylate. The ionizing radiation curable resin composition may further contain at least one of epoxy (meth)acrylate, polyester (meth)acrylate, polyether (meth)acrylate, polycarbonate (meth)acrylate, and acrylic (meth)acrylate as an ionizing radiation curable compound in addition to the urethane (meth)acrylate.

[0036] The ionizing radiation curable resin composition preferably contains a caprolactone-based urethane (meth)acrylate as the urethane (meth)acrylate. The ionizing radiation curable resin composition may also contain a caprolactone-based urethane (meth)acrylate and a urethane (meth)acrylate that is not modified with caprolactone. In this case, the content of the caprolactone-based urethane (meth)acrylate contained in the first protective layer is set to M CLUA The content of urethane (meth)acrylate not modified with caprolactone is M UA Let us assume that UA and M. CLUA M for the sum of CLUA Mass ratio (M CLUA / (M UA +M CLUA )) is, for example, 10% by mass or more and 90% by mass or less, alternatively 20% by mass or more and 80% by mass or less, or alternatively 30% by mass or more and 70% by mass or less.

[0037] When the ionizing radiation curable compound contains a caprolactone-based urethane (meth)acrylate, the number of functional groups of the caprolactone-based urethane (meth)acrylate is preferably from 2 to 9, and more preferably from 2 to 5. By setting the number of functional groups of the caprolactone-based urethane (meth)acrylate within the above range, it is easy to adjust the indentation hardness of the cross section of the first protective layer to the above range.

[0038] Caprolactone-based urethane (meth)acrylate can usually be obtained by reacting caprolactone-based polyol, organic isocyanate, and hydroxy (meth)acrylate. For example, the synthesis method includes reacting polycaprolactone-based polyol with organic polyisocyanate to generate a polyurethane prepolymer containing -NCO groups (isocyanate groups) at both ends, and then reacting it with hydroxy (meth)acrylate.

[0039] As the caprolactone-based polyol, commercially available products can be used, preferably those having two hydroxyl groups and a number average molecular weight of preferably 500 to 3000, more preferably 750 to 2000. In addition, polyols other than caprolactone-based polyols, such as ethylene glycol, diethylene glycol, 1,4-butanediol, 1,6-hexanediol, etc., can be used by mixing one or more polyols at any ratio. As the organic polyisocyanate, diisocyanates having two isocyanate groups are preferred, and from the viewpoint of suppressing yellowing, isophorone diisocyanate, hexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, trimethylhexamethylene diisocyanate, etc. are preferred. As the hydroxy(meth)acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, caprolactone-modified 2-hydroxyethyl acrylate, etc. are preferred.

[0040] When using a caprolactone-based polyol, the caprolactone-based urethane (meth)acrylate is preferably a caprolactone diol-based urethane (meth)acrylate. The caprolactone diol-based urethane (meth)acrylate refers to a urethane (meth)acrylate having a diethylene glycol terminal among caprolactone-based urethane (meth)acrylates. By using the caprolactone diol-based urethane (meth)acrylate, it is possible to suppress the occurrence of cracks and whitening in the first protective layer.

[0041] The number average molecular weight of the ionizing radiation curable compound is, for example, from 1,000 to 10,000, and may be from 2,000 to 10,000. The number average molecular weight is an average molecular weight measured by GPC analysis and converted into standard polystyrene.

[0042] For example, when the ionizing radiation curable compound is an ultraviolet ray curable compound, the ionizing radiation curable compound preferably contains at least one of a photopolymerization initiator and a photopolymerization accelerator. Examples of the photopolymerization initiator include acetophenone, benzophenone, α-hydroxyalkylphenone, Michler's ketone, benzoin, benzyl dimethyl ketal, benzoyl benzoate, α-acyloxime ester, acylphosphine oxide, and thioxanthones. Examples of the photopolymerization accelerator include p-dimethylaminobenzoic acid isoamyl ester and p-dimethylaminobenzoic acid ethyl ester.

[0043] The first curable resin composition may be a thermosetting resin composition. Details of the thermosetting resin composition are the same as those described in "2. Second Protective Layer" below.

[0044] (3) Weatherproofing agent The first protective layer usually contains a weatherproofing agent. Examples of the weatherproofing agent include an ultraviolet absorbing agent and a light stabilizer. The first protective layer preferably contains at least one of an ultraviolet absorbing agent and a light stabilizer. The first protective layer may contain one or more ultraviolet absorbing agents. Similarly, the first protective layer may contain one or more light stabilizers.

[0045] Examples of the ultraviolet absorbing agent contained in the first protective layer include organic ultraviolet absorbing agents such as triazine-based ultraviolet absorbing agents, benzotriazole-based ultraviolet absorbing agents, benzophenone-based ultraviolet absorbing agents, oxybenzophenone-based ultraviolet absorbing agents, salicylic acid ester-based ultraviolet absorbing agents, and cyano(meth)acrylate-based ultraviolet absorbing agents, and inorganic ultraviolet absorbing agents such as titanium dioxide, cerium oxide, and zinc oxide. Among these, triazine-based ultraviolet absorbing agents are more preferable.

[0046] Examples of triazine-based ultraviolet absorbers include hydroxyphenyl triazine-based ultraviolet absorbers. Examples of hydroxyphenyl triazine-based ultraviolet absorbers include 2-(2-hydroxy-4-[1-octyloxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine, 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2,4-bis[2-hydroxy-4-butoxyphenyl]-6-(2,4-dibutoxyphenyl)-1,3,5-triazine, azine, 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2-[4-[(2-hydroxy-3-(2'-ethyl)hexyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, and 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5[2-(2-ethylhexanoyloxy)ethoxy]phenol.

[0047] The content of the ultraviolet absorber in the first protective layer is, for example, 0.5 parts by mass to 10 parts by mass, alternatively 0.8 parts by mass to 8 parts by mass, or alternatively 1 part by mass to 5 parts by mass, relative to 100 parts by mass of the ionizing radiation curable compound. If the content of the ultraviolet absorber is high, bleeding out of the ultraviolet absorber may occur, whereas if the content of the ultraviolet absorber is low, sufficient ultraviolet absorbing performance may not be obtained.

[0048] The light stabilizer contained in the first protective layer may be, for example, a hindered amine light stabilizer. Examples of the hindered amine light stabilizer include 1,2,2,6,6-pentamethyl-4-piperidinyl methacrylate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate, bis(2,2,6,6-pentamethyl-4-piperidyl)sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate, methyl(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate, and 2,4-bis[N-butyl-N-(1-cyclohexyloxy-2,2,6,6-tetramethylpiperidin-4-yl)amino]-6-(2-hydroxyethylamine)-1,3,5-triazine).

[0049] The content of the light stabilizer in the first protective layer is, for example, 1 part by mass to 10 parts by mass, or may be 1.5 parts by mass to 8 parts by mass, or may be 2 parts by mass to 5 parts by mass, relative to 100 parts by mass of the ionizing radiation curable compound. If the content of the light stabilizer is high, bleeding out of the light stabilizer may occur, and if the content of the light stabilizer is low, sufficient light stability may not be obtained.

[0050] (4) Additives The first protective layer may contain additives such as a silicone compound, a polymerization inhibitor, a crosslinking agent, an antistatic agent, an adhesion improver, an antioxidant, a leveling agent, a thixotropy imparting agent, a coupling agent, a plasticizer, an antifouling agent, an antifoaming agent, a filler, an anti-wear agent, an antibacterial agent, an antiviral agent, and an antifungal agent.

[0051] (5) First protective layer The thickness of the first protective layer is, for example, from 2 μm to 20 μm, or may be from 3 μm to 15 μm, or may be from 4 μm to 10 μm. If the first protective layer is too thin, sufficient weather resistance may not be obtained, and if the first protective layer is too thick, cracks may easily occur in the first protective layer, and good adhesion may not be obtained.

[0052] 2.Second protective layer The transfer sheet according to the present disclosure has a second protective layer. The second protective layer and the first protective layer may be disposed so as to be in direct contact with each other, or may be disposed via another layer.

[0053] (1) Indentation hardness In the present disclosure, when a cross-sectional sample piece of a transfer sheet is prepared using a resin embedding method and a microtome, the indentation hardness of the cross-section of the second protective layer is usually 2 MPa or more, may be 5 MPa or more, or may be 10 MPa or more. On the other hand, the indentation hardness of the cross-section of the second protective layer is usually 50 MPa or less, may be 40 MPa or less, or may be 30 MPa or less. If the indentation hardness of the cross-section of the second protective layer is high, the adhesion (especially the initial adhesion) with the first protective layer may be reduced. The method of preparing the cross-sectional sample piece of the transfer sheet and the method of measuring the indentation hardness of the cross-section of the second protective layer are the same as those described for the first protective layer above.

[0054] (2) Resin component The second protective layer contains a cured product (crosslinked structure) of the second curable resin composition. The cured product of the second curable resin composition contains a (meth)acrylic component and a urethane component. The proportion of the cured product of the second curable resin composition is, for example, 70% by mass or more, or may be 90% by mass or more, 95% by mass or more, or may be 100% by mass, based on the total resin components constituting the second protective layer.

[0055] The second curable resin composition may be, for example, a thermosetting resin composition. The thermosetting resin composition is a composition containing at least a thermosetting resin, and is a composition that is cured by heating. The thermosetting resin composition preferably contains at least a urethane (meth)acrylic resin as a thermosetting resin. The second curable resin composition may further contain at least one of a (meth)acrylic resin, a urethane resin, a phenolic resin, a urea melamine resin, an epoxy resin, an unsaturated polyester resin, and a silicone resin as a thermosetting resin in addition to the urethane (meth)acrylic resin. The thermosetting resin composition may further contain a curing agent such as an isocyanate curing agent or an epoxy curing agent.

[0056] In addition, when the second curable resin composition contains a urethane (meth)acrylic resin, the urethane (meth)acrylic resin is preferably a urethane (meth)acrylic copolymer, more preferably a polycarbonate-based urethane (meth)acrylic copolymer. The polycarbonate-based urethane (meth)acrylic copolymer is a resin obtained by radically polymerizing a (meth)acrylic monomer with a polycarbonate-based polyurethane polymer obtained by reacting a polycarbonate diol with a (di)isocyanate.

[0057] Examples of the (di)isocyanate include aromatic isocyanates such as 4,4'-diphenylmethane diisocyanate, 2,4-tolylene diisocyanate, 1,5-naphthalene diisocyanate, n-isocyanate phenylsulfonyl isocyanate, o-isocyanate phenylsulfonyl isocyanate, and p-isocyanate phenylsulfonyl isocyanate; aliphatic isocyanates such as 1,6-hexamethylene diisocyanate; and alicyclic isocyanates such as isophorone diisocyanate, hydrogenated xylylene diisocyanate, and hydrogenated diphenylmethane diisocyanate.

[0058] Examples of the (meth)acrylic monomer include (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, and isobutyl (meth)acrylate.

[0059] In the polycarbonate-based urethane (meth)acrylic copolymer, the mass ratio of the urethane component to the total of the (meth)acrylic component and the urethane component ([urethane component] / ([(meth)acrylic component]+[urethane component]) is, for example, 65% by mass or more and 95% by mass or less, and may be 70% by mass or more and 90% by mass or less. By setting the mass ratio to 65% by mass or more, the proportion of the polycarbonate structure in the polycarbonate-based urethane (meth)acrylic copolymer can be increased, and the structure of the polycarbonate-based urethane acrylic copolymer becomes more rigid. Therefore, the indentation hardness of the cross section of the second protective layer can be adjusted to a predetermined value or more. Furthermore, by setting the mass ratio to 95% by mass or less, the indentation hardness of the cross section of the second protective layer can be adjusted to a predetermined value or less.

[0060] (3) Weatherproofing agent The second protective layer usually contains a weathering agent. Examples of weathering agents include an ultraviolet absorber and a light stabilizer. The second protective layer preferably contains at least one of an ultraviolet absorber and a light stabilizer. The preferred types and modes of the weathering agent are the same as those described in "1. First Protective Layer" above, and therefore will not be described here. In particular, the second protective layer preferably contains a triazine-based ultraviolet absorber. In addition, the second protective layer preferably contains a hindered amine-based light stabilizer.

[0061] The content of the ultraviolet absorber in the second protective layer is, for example, 0.1 parts by mass or more and 50 parts by mass or less, or may be 3 parts by mass or more and 40 parts by mass or less, or may be 10 parts by mass or more and 35 parts by mass or less, relative to 100 parts by mass of the resin component. The content of the ultraviolet absorber in the second protective layer (content relative to 100 parts by mass of the resin component) may be greater than the content of the ultraviolet absorber in the first protective layer (content relative to 100 parts by mass of the resin component).

[0062] The content of the light stabilizer in the second protective layer is, for example, 0.1 to 15 parts by mass, or 1 to 15 parts by mass, or 3 to 10 parts by mass, relative to 100 parts by mass of the resin component. The content of the light stabilizer in the second protective layer (content relative to 100 parts by mass of the resin component) may be greater than the content of the light stabilizer in the first protective layer (content relative to 100 parts by mass of the resin component).

[0063] (4) Additives The second protective layer may contain additives such as a silicone compound, a polymerization inhibitor, a crosslinking agent, an antistatic agent, an adhesion improver, an antioxidant, a leveling agent, a thixotropy imparting agent, a coupling agent, a plasticizer, an antifouling agent, an antifoaming agent, a filler, and an antiblocking agent.

[0064] (5)Second protective layer The thickness of the second protective layer is, for example, 2 μm to 10 μm, may be 3 μm to 8 μm, or may be 3 μm to 5 μm. If the second protective layer is thin, the adhesion (particularly initial adhesion) with the first protective layer may be low. On the other hand, if the second protective layer is thick, the movement of the second protective layer may be large in an environment where temperature changes are repeated, and good weather-resistant adhesion may not be obtained.

[0065] 3. Transfer layer The transfer sheet in the present disclosure has a release film and a transfer layer disposed on one side of the release film. The transfer layer has at least a first protective layer and a second protective layer in order from the release film side. The transfer layer may have a first protective layer and a second protective layer, and may further have other layers. Examples of the other layers include a design layer and an adhesive layer. The transfer layer may have an adhesive layer on the surface of the second protective layer opposite to the first protective layer. The transfer layer may also have a design layer on the surface of the second protective layer opposite to the first protective layer. The transfer layer may also have a first protective layer, a second protective layer, a design layer, and an adhesive layer in order from the release film side.

[0066] The thickness of the transfer layer is, for example, 8 μm or more, may be 10 μm or more, may be 12 μm or more, may be 14 μm or more. If the transfer layer is thin, there is a possibility that sufficient weather resistance cannot be obtained. On the other hand, the thickness of the transfer layer is, for example, 50 μm or less, may be 40 μm or less, may be 30 μm or less.

[0067] (1) Adhesive layer The transfer sheet in the present disclosure may or may not have an adhesive layer on the side of the second protective layer opposite to the first protective layer. When the transfer sheet in the present disclosure includes a design layer described later, the transfer sheet in the present disclosure may have an adhesive layer on the side of the design layer opposite to the second protective layer.

[0068] The adhesive layer is preferably a layer that contacts the substrate and is a component of the transfer layer in the transfer sheet. In this case, the adhesive layer is disposed to improve adhesion between the transfer layer and the substrate. The adhesive layer may contain a component having adhesive properties. Examples of the adhesive component include (meth)acrylic resins, vinyl chloride-vinyl acetate copolymers, vinyl acetate resins, ester resins, epoxy resins, imide resins, and rubber resins.

[0069] The adhesive layer may be a so-called pressure-sensitive adhesive layer. The pressure-sensitive adhesive layer has adhesiveness at room temperature. Examples of the resin contained in the pressure-sensitive adhesive layer include (meth)acrylic resins, silicone resins, vinyl resins, ester resins, urethane resins, amide resins, epoxy resins, rubber resins, and ionomer resins.

[0070] The adhesive layer may be a so-called heat seal layer. The heat seal layer exhibits adhesion by heat. Examples of the resin contained in the heat seal layer include thermoplastic resins. Examples of the thermoplastic resin include acrylic resins, polyacrylic polyols, urethane resins, vinyl chloride resins, vinyl acetate resins, vinyl chloride-vinyl acetate copolymers, styrene-acrylic copolymers, acrylic-vinyl acetate copolymers, polyester resins, amide resins, cyanoacrylate resins, and epoxy resins, and these can be used alone or in combination of two or more kinds. Among these, it is preferable to use at least one of acrylic resins, polyacrylic polyols, and urethane resins in order to improve the processability during the manufacture of the exterior member and the adhesion between the transfer layer and the substrate. In particular, acrylic resins are preferable.

[0071] When a cross-sectional sample piece of the transfer sheet is prepared using a resin embedding method and a microtome, the indentation hardness of the cross-section of the adhesive layer is not particularly limited, but may be, for example, 100 MPa or more and 300 MPa or less, 120 MPa or more and 270 MPa or less, or 140 MPa or more and 250 MPa or less. If the indentation hardness of the cross-section of the adhesive layer is within the above range, for example, good weather-resistant adhesion can be obtained between the design layer and the adhesive layer. The method of preparing the cross-sectional sample piece of the transfer sheet and the method of measuring the indentation hardness of the adhesive layer are the same as those described for the first protective layer above.

[0072] The thickness of the adhesive layer is, for example, from 1 μm to 30 μm, or may be from 2 μm to 10 μm, or may be from 3 μm to 8 μm, or may be from 3 μm to 5 μm. When the thickness of the adhesive layer is within the above range, it is easy to improve the adhesion between the adhesive layer and the base when producing the exterior member.

[0073] In the present disclosure, the adhesive layer may contain a colorant. Examples of the colorant include the colorant in the design layer described below. When the adhesive layer contains a colorant, the transfer layer can be given a design. That is, the adhesive layer may share the function of the design layer described below.

[0074] (2) Design layer The transfer sheet of the present disclosure may or may not have a design layer on the side of the second protective layer opposite to the first protective layer. By providing a design layer, the design of the exterior member is improved. The design layer and the second protective layer may be arranged so as to be in direct contact with each other, or may be arranged via another layer.

[0075] Examples of the design layer include a solid layer (a layer coated with ink) and a pattern layer (a layer printed with ink). The transfer sheet may have a pattern layer and a solid layer in this order from the release film side as the design layer. Examples of the pattern in the pattern layer include wood grain, stone grain, sand grain, tiled pattern, brickwork pattern, cloth grain pattern, leather-squeezed pattern, geometric figures, letters, symbols, abstract patterns, and floral patterns.

[0076] The design layer usually contains a colorant and a binder resin. Examples of the colorant include inorganic pigments such as carbon black (ink), iron black, titanium white, antimony white, yellow lead, titanium yellow, red iron oxide, cadmium red, ultramarine blue, and cobalt blue, organic pigments (including dyes) such as quinacridone red, isoindolinone yellow, nickel azo complex, phthalocyanine blue, and azomethine azo black, metal pigments such as aluminum and brass, and pearl pigments such as titanium dioxide-coated mica and basic lead carbonate.

[0077] Examples of the binder resin include urethane resin, acrylic polyol resin, (meth)acrylic resin, ester resin, amide resin, butyral resin, styrene resin, urethane acrylic copolymer, vinyl chloride-vinyl acetate copolymer, vinyl chloride-vinyl acetate-acrylic copolymer, chlorinated propylene resin, nitrocellulose resin, and cellulose acetate resin. Among them, it is more preferable to use an acrylic polyol resin in combination with a urethane resin.

[0078] When a cross-sectional sample piece of the transfer sheet is prepared using a resin embedding method and a microtome, the indentation hardness of the cross-section of the design layer is not particularly limited, but may be, for example, 100 MPa or more and 300 MPa or less, 120 MPa or more and 270 MPa or less, or 140 MPa or more and 250 MPa or less. If the indentation hardness of the cross-section of the design layer is within the above range, for example, good weather-resistant adhesion can be obtained between the adhesive layer or the second protective layer. The method of preparing the cross-sectional sample piece of the transfer sheet and the method of measuring the indentation hardness of the design layer are the same as those described for the first protective layer above.

[0079] The design layer may contain additives such as ultraviolet absorbers, light stabilizers, hardeners, plasticizers, catalysts, etc., as necessary. The thickness of the design layer is, for example, 0.5 μm or more and 20 μm or less, or may be 1 μm or more and 10 μm or less, or may be 2 μm or more and 5 μm or less.

[0080] (3) Second release film The transfer sheet in the present disclosure may have a second release film on the surface of the second protective layer opposite to the first protective layer. For example, when the transfer sheet is wound into a roll shape and manufactured, the occurrence of blocking can be suppressed. The second release film is usually peeled off from the transfer sheet before the adhesion process described later. Details of the second release film are the same as those described for the first release film described later, so the description here is omitted.

[0081] 4.Release film The transfer sheet in the present disclosure has a release film (first release film) on the side of the first protective layer opposite to the second protective layer. The release film and the first protective layer may be arranged so as to be in direct contact with each other, or may be arranged via another layer.

[0082] The release film preferably contains a resin film, for example, an ester resin, an olefin resin, a styrene resin, a vinyl resin, a (meth)acrylic resin, an amide resin, an imide resin, or a carbonate resin.

[0083] The resin film preferably contains an ester-based resin or an olefin-based resin. Examples of ester-based resins include polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), and polyethylene terephthalate-isophthalate copolymers. Among these, PET or PBT is preferred, and PET is more preferred, from the viewpoint of being less susceptible to thermal shrinkage during the production of the transfer sheet and shrinkage due to irradiation with ionizing radiation.

[0084] Examples of olefin resins include polyethylene, polypropylene, polybutene, ethylene-propylene copolymer, and ethylene-propylene-butene copolymer. Among these, polypropylene is preferred from the viewpoint of being less susceptible to thermal shrinkage during the production of the transfer sheet and shrinkage due to irradiation with ionizing radiation.

[0085] The resin film may be a stretched film or an unstretched film. The stretch ratio in the machine direction (MD) of the stretched film is, for example, 5 times or more and 30 times or less. The stretch ratio in the width direction (TD) of the stretched film is, for example, 5 times or more and 30 times or less. The thickness of the release film is, for example, 10 μm or more and 200 μm or less, may be 15 μm or more and 150 μm or less, or may be 20 μm or more and 100 μm or less.

[0086] As the release film in the present disclosure, a mirror film or a low gloss film can be used depending on the desired surface shape of the first protective layer.

[0087] When the release film is a low gloss film, the 60° gloss value of the first surface located on the opposite side of the release film from the transfer layer side is, for example, 90 or more, may be 100 or more, or may be 110 or more. When the 60° gloss value of the first surface is the above value or more, the transfer sheet has excellent visibility of the design even without peeling off the release film. Therefore, it is possible to inspect for defects without peeling off the release film, improving workability. In addition, since the release film can be used as it is as a masking, it is possible to reduce the amount of plastic used. On the other hand, the 60° gloss value of the first surface of the release film is, for example, 200 or less, may be 160 or less, or may be 140 or less.

[0088] The 60° gloss value of the first side of the release film is a value measured by the following method: The release film peeled off from the transfer sheet is placed on a non-glossy black mount with the first side facing up, and the 60° specular gloss is measured using a gloss meter ("Micro Trigloss (model name)", manufactured by BYK Gardner) in accordance with Method 3 of JIS Z 8741:1997.

[0089] In addition, the 60° gloss value of the second surface located on the transfer layer side of the release film is, for example, 40 or less, may be 35 or less, or may be 30 or less. If the 60° gloss value of the second surface of the release film is the above value or less, the transfer layer after the release film is peeled off will exhibit a low gloss feeling. On the other hand, the 60° gloss value of the second surface is, for example, 3.0 or more, may be 5.0 or more, or may be 10 or more. If the 60° gloss value of the second surface is low, the resin of the first protective layer may get into a fine matte shape, making peeling difficult. In addition, it may not be possible to form the desired shape.

[0090] The 60° gloss value of the second surface of the release film is a value measured by the following method. The release film peeled off from the transfer sheet is placed on a non-glossy black mount with the second side facing up, and the 60° specular gloss is measured using a gloss meter ("Micro Trigloss (model name)", manufactured by BYK Gardner) in accordance with Method 3 of JIS Z 8741:1997.

[0091] The maximum height Rz of the first surface is, for example, 0.8 μm or less, may be 0.6 μm or less, or may be 0.4 μm or less. Rz (maximum height) is one of the peak and height parameters of a profile curve defined in JIS B0601:2013, and is the sum of the height of the highest peak and the depth of the deepest valley in the profile curve in the reference length. Therefore, when Rz (maximum height) is in the above range, diffuse reflection of light is suppressed, and the visibility of the design is improved. On the other hand, the maximum height Rz of the first surface is, for example, 0.1 μm or more, and may be 0.2 μm or more.

[0092] The maximum height Rz of the first surface of the release film is a value measured using the following measuring device and conditions in a rectangular measurement area (1024 μm×768 μm) at any location on the first surface of the release film. Measurement equipment: Shape analysis laser microscope (VK-X1000, manufactured by Keyence Corporation) Objective lens: 50x Measurement mode: Shape measurement mode Measurement pitch: 12μm Measurement quality: High speed mode Scan mode: Laser confocal

[0093] In this specification, Rz (maximum height) is the average value of measurements taken at any ten points.

[0094] The release film has a maximum height Rz of the second surface of, for example, 2.0 μm or more, may be 3.0 μm or more, or may be 4.0 μm or more. If the maximum height Rz of the second surface is low, the transfer layer after the release film is peeled off is less likely to exhibit a low gloss feeling. On the other hand, the maximum height Rz of the second surface is, for example, 6.0 μm or less, and may be 5.0 μm or less. The maximum height Rz of the second surface is a value measured with respect to the second surface of the release film by a method similar to the method for measuring the maximum height Rz of the first surface.

[0095] The release film in the present disclosure is not particularly limited, and may be a single layer or may have a multi-layer structure.When the release film is a low-gloss film, for example, it is preferable that the release film has a film layer including the above-mentioned first surface and a matte layer that is disposed on the transfer layer side of the film layer and includes the above-mentioned second surface.

[0096] (i) Film Layer The film layer is not particularly limited as long as it has the above-mentioned first surface, but is preferably the above-mentioned resin film.

[0097] (ii) Matte layer The mat layer is not particularly limited as long as it has the above-mentioned second surface, and may contain, for example, a resin component and particles as a matting agent. Hereinafter, a matting layer containing a resin component and particles as a matting agent is referred to as a first matting layer. The resin component in the first matting layer is typically a cured product (crosslinked structure) of a curable resin. On the other hand, the resin component may be a thermoplastic resin. In particular, the first matting layer preferably contains a cured product of a curable resin. When the first matting layer contains a cured product of a curable resin, the releasability from the first protective layer is improved.

[0098] When the second surface of the release film is the surface of the first matte layer, the above-mentioned 60° gloss value and maximum height Rz can be adjusted by selecting the type of particles, adjusting the average particle size and content, and the like.

[0099] Examples of the curable resin include ionizing radiation curable resins and thermosetting resins. Examples of the ionizing radiation curable resin include electron beam curable resins and ultraviolet ray curable resins.

[0100] The ionizing radiation curable resin (ionizing radiation curable compound) is not limited as long as it undergoes a crosslinking polymerization reaction upon irradiation with ionizing radiation and changes into a three-dimensional polymer structure. Examples of the ionizing radiation curable resin include prepolymers, oligomers, and monomers having polymerizable unsaturated bonds or epoxy groups in the molecule that can be crosslinked upon irradiation with ionizing radiation. In the present disclosure, only one type of ionizing radiation curable resin may be used, or two or more types may be used. Among them, it is preferable to use at least one of a polyfunctional monomer and an oligomer as the ionizing radiation curable resin.

[0101] Examples of ionizing radiation curable resins include (meth)acrylate-based resins such as urethane (meth)acrylate, ester (meth)acrylate, and epoxy (meth)acrylate; silicon-based resins such as siloxane; ester-based resins; and epoxy-based resins. (Meth)acrylate-based resins refer to acrylate-based resins or methacrylate-based resins.

[0102] The weight average molecular weight of the ionizing radiation curable resin is, for example, from 500 to 80,000, and may be from 1,000 to 50,000. The weight average molecular weight is a value measured by gel permeation chromatography (GPC) using polystyrene as a standard substance.

[0103] The ionizing radiation curable resin preferably contains at least a polyfunctional monomer or oligomer having a weight average molecular weight of at least 500. Examples of such polyfunctional monomers or oligomers include (meth)acrylate-based resins such as dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, urethane (meth)acrylate, ester (meth)acrylate, and epoxy (meth)acrylate.

[0104] On the other hand, examples of thermosetting resins include unsaturated ester resins, urethane resins (including two-component curing polyurethanes), epoxy resins, aminoalkyd resins, phenolic resins, urea resins, diallyl phthalate resins, melamine resins, guanamine resins, melamine urea co-condensation resins, silicon resins, and siloxane resins.

[0105] Examples of the particles include inorganic particles and synthetic resin particles. Examples of the inorganic particles include silica, alumina, calcium carbonate, magnesium carbonate, calcium sulfate, barium sulfate, and kaolin. Examples of the synthetic resin particles include acrylic beads, urethane beads, nylon beads, silicone beads, silicone rubber beads, polycarbonate beads, and polyolefin wax (e.g., polypropylene wax, polyethylene wax).

[0106] The average particle size of the particles is preferably 1.0 μm or more and 10 μm or less, and more preferably 2.0 μm or more and 8.0 μm or less.

[0107] The content of the particles in the first mat layer is preferably 3 parts by mass or more and 80 parts by mass or less, and more preferably 5 parts by mass or more and 60 parts by mass or less, based on 100 parts by mass of the resin component.

[0108] The first matte layer may contain additives such as a release agent, an ultraviolet absorber, an infrared absorber, a light stabilizer, a polymerization inhibitor, a crosslinking agent, an antistatic agent, an antioxidant, a leveling agent, a coupling agent, a plasticizer, an antifoaming agent, a filler, a thermal radical generator, an aluminum chelating agent, etc. The thickness of the first matte layer is not particularly limited, but is, for example, 0.1 μm or more and 10 μm or less.

[0109] The first matte layer can be obtained, for example, by applying a matte layer-forming ink containing a curable resin onto one surface of the film layer and curing the ink.

[0110] The mat layer may be, for example, a layer (second mat layer) having an uneven shape formed by irregular wrinkles on one side. The material and forming method of the release layer described in JP 2022-149930 A can be used as the material and forming method of such a second mat layer.

[0111] The first matte layer and the second matte layer may be formed on the entire surface of one side of the film layer, or may be formed on a partial area of ​​one side of the film layer. The entire surface of one side of the film layer refers to 90% or more of the area of ​​one side of the film layer. The matte layer may be arranged so as to cover 95% or more of one side of the film layer, or may be arranged so as to cover 100%. On the other hand, the matte layer may be arranged so as to cover 50% or less of one side of the film layer, or may be arranged so as to cover 40% or less, or may be arranged so as to cover 30% or less.

[0112] In addition, the low gloss film is not limited to a structure having a film layer and a matte layer as described above, but may be a single layer. For example, a matte film in which the particles exemplified in the first matte layer are kneaded can be used. In this case, the 60° gloss value and Rz of the first surface located on the opposite side to the transfer layer side and the second surface located on the transfer layer side are approximately the same.

[0113] B. Method of manufacturing transfer sheet FIG. 2 is a schematic cross-sectional view illustrating a method for producing a transfer sheet in the present disclosure. First, as shown in FIG. 2(a), a release film 1 is prepared. Next, as shown in FIG. 2(b), a first composition containing a first curable resin composition and a weather resistance agent is applied to the surface of the release film 1 and cured to form a first protective layer 2. Next, as shown in FIG. 2(c), a second composition containing a second curable resin composition and a weather resistance agent is applied to the surface of the first protective layer 2 opposite to the release film 1 and cured to form a second protective layer 3. This allows the release film 1, the first protective layer 2, and the second protective layer 3 to be arranged in a thickness direction D. TA transfer sheet 10 having the above-mentioned components in this order can be obtained. In Fig. 2, the transfer layer X corresponds to the first protective layer 2 and the second protective layer 3. When a cross-sectional sample piece of the transfer sheet 10 is prepared using a resin embedding method and a microtome, the indentation hardness of the cross-section of the first protective layer 2 is within a predetermined range, and the indentation hardness of the cross-section of the second protective layer 3 is also within a predetermined range.

[0114] According to the present disclosure, for the reasons described above, a transfer sheet for exterior components having good weather-resistant adhesion and scratch resistance can be obtained.

[0115] 1. First protective layer formation process The first protective layer forming step in the present disclosure is a step of applying a first composition containing the first curable resin composition and a weathering agent to the surface of the release film, curing the composition, and forming the first protective layer. The first composition is a composition for forming the first protective layer. The first curable resin composition and the weathering agent are the same as those described in "A. Transfer sheet" above, so the description here is omitted.

[0116] Examples of the method for applying the first composition include gravure printing, bar coating, roll coating, reverse roll coating, and comma coating. The first coating layer is obtained by applying the first composition. Examples of the method for curing the first coating layer include a method of irradiating with ionizing radiation such as electron beams and ultraviolet rays, and a method of applying heat.

[0117] 2.Second protective layer formation process The second protective layer forming step in the present disclosure is a step of applying a second composition containing the second curable resin composition and a weathering agent to the surface of the first protective layer opposite to the release film, and curing the composition to form the second protective layer. The second composition is a composition for forming the second protective layer. The second curable resin composition and the weathering agent are the same as those described in "A. Transfer sheet" above, so the description here is omitted.

[0118] Examples of the method for applying the second composition include gravure printing, bar coating, roll coating, reverse roll coating, and comma coating. By applying the second composition, a second coating layer is obtained. Examples of the method for curing the second coating layer include a method of applying heat.

[0119] 3.Other processes The method for producing a transfer sheet in the present disclosure may include a step of forming a layer belonging to the transfer layer described above in addition to the first protective layer forming step and the second protective layer forming step. For example, the method for producing a transfer sheet in the present disclosure may include an adhesive layer forming step of forming an adhesive layer on the surface of the second protective layer opposite to the first protective layer. The adhesive layer can be formed by applying a composition for forming an adhesive layer by a known method such as gravure printing, bar coating, roll coating, reverse roll coating, or comma coating, and drying and curing as necessary. For example, the method for producing a transfer sheet in the present disclosure may include a design layer forming step of forming a design layer on the surface of the second protective layer opposite to the first protective layer. The design layer can be formed, for example, by applying an ink containing a colorant, a binder resin, and a solvent to the surface of the second protective layer opposite to the first protective layer. In addition, the transfer sheet obtained by each of the above-mentioned steps is the same as the contents described in the above "A. Transfer sheet", so the description here is omitted.

[0120] C. Manufacturing method of exterior components 3 is a schematic cross-sectional view illustrating a method for producing an exterior member according to the present disclosure. First, as shown in FIG. 3(a), a transfer sheet 10 is prepared. The transfer sheet 10 shown in FIG. 3(a) is a sheet in which a release film 1, a first protective layer 2, a second protective layer 3, and an adhesive layer 4 are arranged in a thickness direction D. TIn this order, the transfer sheet 10 has the second protective layer 3 side and the substrate 20, as shown in FIG. 3(b), and the two are brought into close contact with each other. The "side of the second protective layer 3 of the transfer sheet 10" refers to the side of the transfer sheet 10 that is located on the second protective layer 3 side when the release film 1 is used as a reference. Since the transfer sheet 10 shown in FIG. 3(a) has an adhesive layer 4, the "side of the second protective layer 3 of the transfer sheet 10" corresponds to the side of the adhesive layer 4. Next, as shown in FIG. 3(c), the release film 1 is peeled off from the transfer sheet 10. This causes the first protective layer 2, the second protective layer 3, the adhesive layer 4, and the substrate 20 to be separated in the thickness direction D. T In this order, the exterior member 100 is obtained.

[0121] According to the present disclosure, by using the above-mentioned transfer sheet, an exterior member having good weather-resistant adhesion and scratch resistance can be obtained.

[0122] 1. Preparation process The preparation step in this disclosure is a step of preparing the transfer sheet described above. The transfer sheet is the same as that described in "A. Transfer sheet" above, so the description here is omitted.

[0123] 2. Adhesion process The adhesion step in the present disclosure is a step of placing the surface of the transfer sheet on the second protective layer side against a substrate and adhering them together. When placing the transfer sheet against the substrate, they may be placed so as to be in direct contact with each other, or may be placed between them via another layer. For example, when the transfer sheet does not have an adhesive layer, an adhesive layer is placed.

[0124] The material for the substrate in the present disclosure is not particularly limited, and can be appropriately selected from among resins, wood, metals, nonmetallic inorganic materials, paper, nonwoven fabrics, woven fabrics, and the like depending on the application.

[0125] An example of the substrate in the present disclosure is a resin member. Examples of resins used in the resin member include vinyl chloride resins, (meth)acrylic resins, ester resins, styrene resins, olefin resins, acrylonitrile-butadiene-styrene copolymers (ABS resins), phenolic resins, cellulose resins, rubber, polycarbonate resins, and melamine resins. The resin member may contain fibers such as carbon fibers, glass fibers, aramid fibers, Zylon fibers, boron fibers, and polyethylene fibers. The strength of the resin member can be improved by containing fibers. Another example of the substrate is a wood member. Examples of the wood member include a wood veneer, wood plywood, particle board, and wood fiber board. Examples of wood used in the wood member include cedar, cypress, pine, and lauan.

[0126] Another example of the substrate is a metal member. Examples of metals used for the metal member include iron and aluminum. Another example of the substrate is a ceramic member. The material of the ceramic member may be ceramics such as glass or porcelain, a non-cement ceramic material such as gypsum, or a non-ceramic ceramic material such as ALC (aerated lightweight concrete). A calcium silicate board may also be used as the ceramic member.

[0127] The substrate may be surface-treated to improve adhesion to the transfer sheet. For example, when the substrate is an aluminum member, examples of the surface treatment include anodizing, chemical conversion treatment, plating, painting, blasting, and polishing. For example, when the substrate is a ceramic member, examples of the surface treatment include UV coating and painting.

[0128] The shape of the substrate is not particularly limited, and may be, for example, a plate, a sheet, or a three-dimensional shape. The substrate may have a flat surface, a curved surface, or both a flat surface and a curved surface. The substrate may have at least one of a convex portion, a concave portion, a convex streak portion, a concave streak portion, and a through portion.

[0129] As the substrate in the present disclosure, among others, an acrylic plate, a polycarbonate plate, a non-combustible plate, a metal plate, a polyvinyl chloride plate, a melamine plate, or a carbon fiber reinforced plastic plate is preferable. As the non-combustible plate, for example, a fiber reinforced cement plate can be mentioned, among others, a calcium silicate plate is preferable.

[0130] In the adhesion step, the surface of the transfer sheet on the second protective layer side is opposed to the substrate, and the two are adhered to each other. Examples of the method for adhering the two include a lamination method. In the lamination method, for example, the laminate of the transfer sheet and the substrate is heated and pressed from the transfer sheet side. Examples of the method for heating and pressing include a method using a roll transfer device. The roll temperature of the roll transfer device is, for example, 200°C or less, and may be 180°C or less. If the roll temperature is high, the transfer sheet may be softened more than necessary. On the other hand, the roll temperature of the roll transfer device is, for example, 100°C or more, and may be 110°C or more, or may be 120°C or more. In addition, the manufacturing method of the exterior member in the present disclosure may have a peeling step of peeling the release film from the first protective layer after the adhesion step.

[0131] 3. Exterior materials The exterior member in the present disclosure has a first protective layer, a second protective layer, an adhesive layer, and a substrate in this order in the thickness direction. The exterior member may be an exterior member with a release film having a release film on the surface of the first protective layer opposite to the second protective layer, or may be an exterior member without a release film.

[0132] The exterior member in the present disclosure is, for example, a building material (an exterior member of an architectural structure). The building material is used, for example, in houses, offices, stores, hospitals, clinics, general roads and highways, agricultural houses, and the like. Examples of uses of the exterior member include exterior walls, roofs, eaves ceilings, door pockets, window frames, doors, door frames, handrails, fences, and clothes drying racks. Specific uses of the exterior member include soundproof walls or windbreak walls on general roads and highways, balcony partitions, fences, roof members for terraces or carports, transparent members constituting agricultural houses, and the like.

[0133] In addition, the exterior member in the present disclosure is used as, for example, exterior members of vehicles, ships and aircraft, exterior members of industrial machines, and exterior members of various lenses, in addition to building materials (exterior members of architectural structures). Exterior members of vehicles include, for example, window materials such as side windows, rear windows, roof windows, front windows and quarter windows; headlight covers, turn signal lamp lenses, reflectors; and pillars. Exterior members of vehicles include, for example, automobiles, railroad cars, construction machines, and light vehicles such as golf carts. Exterior materials of industrial machines include, for example, window materials for visibility in machine tools. Exterior lenses include, for example, traffic light lenses.

[0134] D. Exterior materials FIG. 4 is a schematic cross-sectional view illustrating an exterior member according to the present disclosure. As shown in FIG. 4(a), the exterior member 100 according to the present disclosure has a first protective layer 2, a second protective layer 3, an adhesive layer 4, and a base 20 in this order in the thickness direction, the first protective layer 2 contains a cured product of the first curable resin composition and a weathering agent, the second protective layer 3 contains a cured product of the second curable resin composition and a weathering agent, and the cured product of the first curable resin composition and the cured product of the second curable resin composition each contain a (meth)acrylic component and a urethane component. In addition, when a cross-sectional sample piece of the exterior member 100 is prepared using a resin embedding method and a microtome, the indentation hardness of the cross section of the first protective layer 2 is 150 MPa or more and 300 MPa or less, and the indentation hardness of the cross section of the second protective layer 3 is 2 MPa or more and 50 MPa or less. Here, the adhesive layer 4 may also have a function as a design layer. Furthermore, as shown in FIG. 4( b ), the exterior member 100 may have a design layer 5 between the second protective layer 3 and the adhesive layer 4 .

[0135] According to the present disclosure, the first protective layer contains a cured product of a predetermined first curable resin composition and a weather resistant agent, and has an indentation hardness in a cross section within a predetermined range, and the second protective layer contains a cured product of a predetermined second curable resin composition and a weather resistant agent, and has an indentation hardness in a cross section within a predetermined range, resulting in an exterior component with excellent scratch resistance and good weather resistant adhesion between the first protective layer and the second protective layer.

[0136] 1.1st protective layer The exterior member according to the present disclosure has a first protective layer. The first protective layer contributes to improving the surface properties (e.g., scratch resistance, abrasion resistance, etc.) of the exterior member. The first protective layer may be the outermost layer of the exterior member.

[0137] In the present disclosure, when a cross-sectional sample piece of an exterior member is prepared using a resin embedding method and a microtome, the indentation hardness of the cross-section of the first protective layer is usually 150 MPa or more, may be 180 MPa or more, or may be 190 MPa or more. If the indentation hardness of the cross-section of the first protective layer is low, good scratch resistance and abrasion resistance may not be obtained. On the other hand, when a cross-sectional sample piece of an exterior member is prepared using a resin embedding method and a microtome, the indentation hardness of the cross-section of the first protective layer is usually 300 MPa or less, may be 280 MPa or less, or may be 250 MPa or less. If the indentation hardness of the cross-section of the first protective layer is high, the conformability of the first protective layer to the second protective layer is low, and good weather-resistant adhesion may not be obtained.

[0138] The method for adjusting the indentation hardness of the cross section of the first protective layer is the same as that described above in "A. Transfer sheet."

[0139] The indentation hardness of the first protective layer of the exterior member is a value obtained by measuring a cross-sectional sample piece prepared using a resin embedding method and a microtome according to the following method. (Method of preparing cross-sectional sample pieces for measurement) A cut sample is prepared by cutting the exterior member to an arbitrary size. The cut sample is embedded in resin (a room temperature curing type two-part epoxy resin) and left at room temperature for 24 hours or more to harden, thereby preparing an embedded sample in which the cut sample is embedded in resin (resin embedding method). The embedded sample is cut vertically using a microtome to expose the cross section of the layer to be measured, thereby preparing a cross-sectional sample piece for indentation hardness measurement. The cutting method for the embedded sample is the same as that described above in "A. Transfer sheet".

[0140] The method for measuring the indentation hardness is the same as that described above in "A. Transfer sheet."

[0141] The resin component, weatherproofing agent, additives and thickness of the first protective layer are the same as those described above in "A. Transfer sheet."

[0142] 2.Second protective layer The exterior member according to the present disclosure has a second protective layer. The second protective layer and the first protective layer may be disposed so as to be in direct contact with each other, or may be disposed via another layer.

[0143] When a cross-sectional sample piece of the exterior member is prepared using a resin embedding method and a microtome, the indentation hardness of the cross-section of the second protective layer is usually 2 MPa or more, may be 5 MPa or more, may be 10 MPa or more, may be 15 MPa or more, or may be 20 MPa or more. On the other hand, the indentation hardness of the cross-section of the second protective layer is usually 50 MPa or less, may be 40 MPa or less, or may be 30 MPa or less. If the indentation hardness of the cross-section of the second protective layer is high, the adhesion (especially the initial adhesion) with the first protective layer may be reduced. The method of preparing the cross-sectional sample piece of the exterior member and the method of measuring the indentation hardness of the cross-section of the second protective layer are the same as those described for the first protective layer above.

[0144] The indentation hardness of the cross section of the second protective layer in the exterior member may be greater than the indentation hardness of the cross section of the second protective layer in the transfer sheet, because it is compressed by the transfer.

[0145] The resin component, weatherproofing agent, additives and thickness of the second protective layer are the same as those described above in "A. Transfer sheet."

[0146] 3.Adhesive layer The exterior member in the present disclosure has an adhesive layer. The adhesive layer may be the same as the adhesive layer described in "A. Transfer sheet" above. In addition, the indentation hardness of the cross section of the adhesive layer in the exterior member may be greater than the indentation hardness of the cross section of the adhesive layer in the transfer sheet. This is because it is compressed by transfer. In the case where the transfer sheet does not have an adhesive layer, the adhesive layer of the exterior member in the present disclosure may be an adhesive layer disposed between the transfer sheet and the substrate.

[0147] 4. Design layer The exterior member of the present disclosure may have a design layer. The design layer may be the same as the design layer described in "A. Transfer sheet" above. In addition, the indentation hardness of the cross section of the design layer of the exterior member may be greater than the indentation hardness of the cross section of the design layer of the transfer sheet. This is because it is compressed by transfer.

[0148] 5.Base The substrate in this disclosure is similar to that described above in "C. Manufacturing method of exterior member," and therefore will not be described here.

[0149] 6. Exterior materials The exterior member in this disclosure is similar to the contents described above in "C. Manufacturing method of exterior member," and therefore will not be described here.

[0150] The present disclosure is not limited to the above-described embodiments. The above-described embodiments are merely examples, and anything that has substantially the same configuration as the technical idea described in the claims of the present disclosure and exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES

[0151] [Example 1] The following composition 1 for forming a first protective layer was applied to one side of a release film 1 (mirror-finished PET film E5001, manufactured by Toyobo Co., Ltd.) in a coating amount of 5 g / m2 after drying. 2 Then, the coating was irradiated with an electron beam (applied voltage: 90 kV, 5 Mrad (50 kGy)) to form a first protective layer having a thickness of 5 μm. <Composition 1 for forming first protective layer> ·Ionizing radiation curable resin composition: 100 parts by mass (Caprolactone-based urethane acrylate: 30 parts by mass) (Pentaerythritol triacrylate (hydroxyl group-containing acrylate): 50 parts by mass) (Acrylate: 20 parts by weight) Triazine-based UV absorber: 2 parts by weight (Hydroxyphenyltriazine UV absorber (product name: TINUVIN479, BASF)) Light stabilizer having a reactive functional group: 2 parts by weight (Product name: Sanol LS-3410, Nippon Nyukazai Co., Ltd.) Solvent: appropriate amount

[0152] Next, the surface of the obtained first protective layer was subjected to a corona discharge treatment, and then the following composition 1 for forming a second protective layer was applied and dried to form a second protective layer having a thickness of 5 μm. <Composition 1 for forming second protective layer> Polycarbonate-based urethane acrylic copolymer: 100 parts by weight (urethane to acrylic ratio is 9:1) Hydroxyphenyltriazine UV absorber: 17 parts by weight (product name: TINUVIN 400, BASF) Hydroxyphenyltriazine UV absorber: 13 parts by weight (product name: TINUVIN 479, BASF) Hindered amine light stabilizer: 8 parts by weight (product name: TINUVIN 123, BASF) Anti-blocking agent: 9 parts by weight (silica particles, average particle size 3 μm) Hardener: 25 parts by weight (hexamethylene diisocyanate) Solvent: appropriate amount

[0153] Next, a heat seal agent containing an acrylic resin (polymethyl methacrylate) was applied to the surface of the obtained second protective layer and dried to form an adhesive layer having a thickness of 5 μm. This resulted in a transfer sheet having a release film, a first protective layer, a second protective layer, and an adhesive layer (heat seal layer) in this order in the thickness direction.

[0154] [Example 2] The composition 2 for forming the first protective layer described below was applied to one surface of the release film 2 prepared by the method described below in such a manner that the coating amount after drying was 5 g / m 2 Then, the coating was irradiated with an electron beam (applied voltage: 90 kV, 5 Mrad (50 kGy)) to form a first protective layer having a thickness of 5 μm.

[0155] <Preparation of release film 2> The following thermosetting resin composition was applied to the corona-treated surface of a 50 μm-thick PET film (E5101, Toyobo Co., Ltd.) at a coating amount of 3 g / m after drying. 2 The mixture was then cured in an oven at 40° C. for 5 days, thereby obtaining a release film having a film layer and a matte layer. <Thermosetting resin composition> Polyester polyol resin: 100 parts by weight Hardener: 15 parts by weight (hexamethylene diisocyanate) Matting agent: 15 parts by weight (silica particles, average particle size 3 μm) Solvent: appropriate amount

[0156] <Composition 2 for forming first protective layer> ·Ionizing radiation curable resin composition: 100 parts by mass (Caprolactone-based urethane acrylate: 30 parts by mass) (Pentaerythritol triacrylate (hydroxyl group-containing acrylate): 70 parts by mass) Triazine-based UV absorber: 2 parts by weight (Hydroxyphenyltriazine UV absorber (product name: TINUVIN479, BASF)) Light stabilizer having a reactive functional group: 2 parts by weight (Product name: Sanol LS-3410, Nippon Nyukazai Co., Ltd.) Solvent: appropriate amount

[0157] Next, the surface of the obtained first protective layer was subjected to a corona discharge treatment, and then the above-mentioned composition 1 for forming the second protective layer was applied and dried to form a second protective layer having a thickness of 5 μm.

[0158] Next, the following ink composition 1 containing a resin component and a pigment was applied by gravure coating to the surface of the obtained second protective layer, and dried to form a design layer having a thickness of 3 to 5 μm including a pattern layer and a solid layer. The adhesive composition 1 containing an acrylic resin and a vinyl chloride-vinyl acetate copolymer in a ratio of 6:4 (mass ratio) was applied by gravure coating to the surface of the obtained design layer, and dried to form an adhesive layer having a thickness of 2 μm. This resulted in a transfer sheet having a release film, a first protective layer, a second protective layer, a design layer, and an adhesive layer in this order in the thickness direction. <Ink composition 1> Resin component of ink (mixture of urethane resin and polyacrylic polyol (mass ratio 20:80)) Pigments (organic and inorganic)

[0159] [Example 3] A first protective layer-forming composition 3 described below was applied to one side of a release film 3 (a PET film having a thickness of 50 μm, haze (Hz): 83%, total light transmittance (Tt): 68%, and 60-degree specular gloss of 16%) containing a matting agent in a coating amount of 5 g / m2 after drying. 2Then, the coating was irradiated with an electron beam (applied voltage: 90 kV, 5 Mrad (50 kGy)) to form a first protective layer having a thickness of 5 μm. <Composition 3 for forming first protective layer> ·Ionizing radiation curable resin composition: 100 parts by mass (Caprolactone-based urethane acrylate: 60 parts by mass) (Urethane acrylate: 40 parts by weight) Triazine-based UV absorber: 2 parts by weight (Hydroxyphenyltriazine UV absorber (product name: TINUVIN479, BASF)) Light stabilizer having a reactive functional group: 2 parts by weight (Product name: Sanol LS-3410, Nippon Nyukazai Co., Ltd.) Solvent: appropriate amount

[0160] Next, the surface of the obtained first protective layer was subjected to a corona discharge treatment, and then the following composition 2 for forming a second protective layer was applied and dried to form a second protective layer having a thickness of 5 μm. <Composition 2 for forming second protective layer> Polycarbonate-based urethane acrylic copolymer: 95 parts by weight (urethane to acrylic ratio is 9:1) Acrylic polyol: 5 parts by weight Hydroxyphenyltriazine UV absorber: 17 parts by weight (product name: TINUVIN 400, BASF) Hydroxyphenyltriazine UV absorber: 13 parts by weight (product name: TINUVIN 479, BASF) Hindered amine light stabilizer: 8 parts by weight (product name: TINUVIN 123, BASF) Anti-blocking agent: 9 parts by weight (silica particles, average particle size 3 μm) Hardener: 25 parts by weight (hexamethylene diisocyanate) Solvent: appropriate amount

[0161] Next, the ink composition 1 containing a resin component and a pigment was applied by gravure coating to the surface of the obtained second protective layer, and dried to form a design layer having a thickness of 3 to 5 μm including a pattern layer and a solid layer. The adhesive composition 1 containing an acrylic resin and a vinyl chloride-vinyl acetate copolymer in a ratio of 6:4 (mass ratio) was applied by gravure coating to the surface of the obtained design layer, and dried to form an adhesive layer having a thickness of 2 μm. This resulted in a transfer sheet having a release film, a first protective layer, a second protective layer, a design layer, and an adhesive layer in this order in the thickness direction.

[0162] [Example 4] The composition 2 for forming the first protective layer was applied to one surface of the release film 3 in a coating amount of 5 g / m2 after drying. 2 Then, the coating was irradiated with an electron beam (applied voltage: 90 kV, 5 Mrad (50 kGy)) to form a first protective layer having a thickness of 5 μm.

[0163] Next, the surface of the obtained first protective layer was subjected to a corona discharge treatment, and then the following composition 3 for forming a second protective layer was applied and dried to form a second protective layer having a thickness of 5 μm.

[0164] <Composition 3 for forming second protective layer> Polycarbonate-based urethane acrylic copolymer: 98 parts by weight (urethane to acrylic ratio is 9:1) Acrylic polyol: 2 parts by weight Hydroxyphenyltriazine UV absorber: 17 parts by weight (product name: TINUVIN 400, BASF) Hydroxyphenyltriazine UV absorber: 13 parts by weight (product name: TINUVIN 479, BASF) Hindered amine light stabilizer: 8 parts by weight (product name: TINUVIN 123, BASF) Anti-blocking agent: 9 parts by weight (silica particles, average particle size 3 μm) Hardener: 25 parts by weight (hexamethylene diisocyanate)

[0165] Next, the ink composition 1 containing a resin component and a pigment was applied by gravure coating to the surface of the obtained second protective layer, and dried to form a design layer having a thickness of 3 to 5 μm including a pattern layer and a solid layer. The adhesive composition 1 containing an acrylic resin and a vinyl chloride-vinyl acetate copolymer in a ratio of 6:4 (mass ratio) was applied by gravure coating to the surface of the obtained design layer, and dried to form an adhesive layer having a thickness of 2 μm. This resulted in a transfer sheet having a release film, a first protective layer, a second protective layer, a design layer, and an adhesive layer in this order in the thickness direction.

[0166] [Example 5] (Manufacture of exterior components) The adhesive layer side of the transfer sheet obtained in Example 1 was placed opposite one side of a substrate (a 2 mm thick acrylic plate ("COMOGLAS", manufactured by Kuraray Co., Ltd.)) and laminated. Using a laminator, the two were heated and pressed from the transfer sheet side at a lamination roll temperature of 170°C and a conveying speed of 2 m / min to adhere them together. The release film was peeled off from the adhered transfer sheet to obtain an exterior member.

[0167] [Example 6] (Preparation of transfer sheet) The composition 2 for forming the first protective layer was applied to one surface of the release film 3 in a coating amount of 5 g / m2 after drying. 2 Then, the coating was irradiated with an electron beam (applied voltage: 90 kV, 5 Mrad (50 kGy)) to form a first protective layer having a thickness of 5 μm.

[0168] Next, the surface of the obtained first protective layer was subjected to a corona discharge treatment, and then the above-mentioned composition 2 for forming the second protective layer was applied and dried to form a second protective layer having a thickness of 5 μm.

[0169] Next, the ink composition 1 containing a resin component and a pigment was applied by gravure coating to the surface of the obtained second protective layer, and then dried to form a design layer having a thickness of 3 to 5 μm including a pattern layer and a solid layer. This resulted in a transfer sheet having a release film, a first protective layer, a second protective layer, and a design layer in this order in the thickness direction.

[0170] (Manufacture of exterior components) A 10 mm thick fireproof board (fiber reinforced cement board) with the transfer surface treated with an epoxy resin sealer was prepared as the substrate. Next, a hot melt adhesive was applied to the design layer side of the transfer sheet obtained above and dried. The epoxy resin sealer treated side of the substrate and the adhesive coated side of the transfer sheet were placed opposite each other and laminated. Using a laminator, the transfer sheet side was heated and pressed to adhere to each other under conditions of a laminating roll temperature of 170°C and a conveying speed of 2 m / min. The release film was peeled off from the adhered transfer sheet to obtain an exterior member.

[0171] [Comparative Example 1] The composition 2 for forming the first protective layer was applied to one surface of the release film 3 in a coating amount of 5 g / m2 after drying. 2 Then, the coating was irradiated with an electron beam (applied voltage: 90 kV, 5 Mrad (50 kGy)) to form a first protective layer having a thickness of 5 μm.

[0172] Next, the surface of the obtained first protective layer was subjected to a corona discharge treatment, and then the following composition 4 for forming a second protective layer was applied and dried to form a second protective layer having a thickness of 5 μm. <Composition 4 for forming second protective layer> Acrylic polyol: 100 parts by weight Hydroxyphenyltriazine UV absorber: 17 parts by weight (product name: TINUVIN 400, BASF) Hydroxyphenyltriazine UV absorber: 13 parts by weight (product name: TINUVIN 479, BASF) Hindered amine light stabilizer: 8 parts by weight (product name: TINUVIN 123, BASF) Anti-blocking agent: 9 parts by weight (silica particles, average particle size 3 μm) Hardener: 25 parts by weight (hexamethylene diisocyanate)

[0173] Next, the ink composition 1 containing a resin component and a pigment was applied by gravure coating to the surface of the obtained second protective layer, and dried to form a design layer having a thickness of 3 to 5 μm including a pattern layer and a solid layer. The adhesive composition 1 containing an acrylic resin and a vinyl chloride-vinyl acetate copolymer in a ratio of 6:4 (mass ratio) was applied by gravure coating to the surface of the obtained design layer, and dried to form an adhesive layer having a thickness of 2 μm. This resulted in a transfer sheet having a release film, a first protective layer, a second protective layer, a design layer, and an adhesive layer in this order in the thickness direction.

[0174] [Comparative Example 2] The following composition 4 for forming a first protective layer was applied to one side of a release film 1 (mirror-finished PET film E5001, manufactured by Toyobo Co., Ltd.) in a coating amount of 5 g / m2 after drying. 2 Then, the coating was irradiated with an electron beam (applied voltage: 90 kV, 5 Mrad (50 kGy)) to form a first protective layer having a thickness of 5 μm. <Composition 4 for forming first protective layer> ·Ionizing radiation curable resin composition: 100 parts by mass (Caprolactone-based urethane acrylate: 100 parts by mass) Hydroxyphenyltriazine UV absorber: 2 parts by weight (product name: TINUVIN 479, BASF) Light stabilizer with reactive functional groups: 2 parts by weight (product name: Sanol LS-3410, Nippon Nyukazai Co., Ltd.)

[0175] Next, the surface of the obtained first protective layer was subjected to a corona discharge treatment, and then the above-mentioned composition 1 for forming the second protective layer was applied and dried to form a second protective layer having a thickness of 5 μm.

[0176] Next, the ink composition 1 containing a resin component and a pigment was applied by gravure coating to the surface of the obtained second protective layer, and dried to form a design layer having a thickness of 3 to 5 μm including a pattern layer and a solid layer. The adhesive composition 1 containing an acrylic resin and a vinyl chloride-vinyl acetate copolymer in a ratio of 6:4 (mass ratio) was applied by gravure coating to the surface of the obtained design layer, and dried to form an adhesive layer having a thickness of 2 μm. This resulted in a transfer sheet having a release film, a first protective layer, a second protective layer, a design layer, and an adhesive layer in this order in the thickness direction.

[0177] [Indentation hardness measurement] The indentation hardness was measured by the above-mentioned method for the first protective layer, the second protective layer, and the heat seal layer (Example 1) or the design layer (Examples 2-4, Comparative Examples 1 and 2) of the transfer sheets obtained in Examples 1 to 4, Comparative Examples 1 and 2. The results are shown in Table 1. The indentation hardness was measured by the above-mentioned method for the first protective layer, the second protective layer, and the heat seal layer or the design layer of the exterior members obtained in Examples 5 and 6. The results are shown in Table 1. The indentation hardness value of Example 6 is the indentation hardness of the first protective layer, second protective layer, and decorative layer in the exterior component measured when a 2 mm thick acrylic plate ("COMOGLAS", manufactured by Kuraray Co., Ltd.) was used as the base instead of the non-flammable board.

[0178] [Evaluation of adhesion (initial stage)] The adhesive layer (design layer) side of the transfer sheets obtained in Examples 1 to 4, Comparative Examples 1 and 2 was faced to one side of a substrate (a 2 mm thick acrylic plate ("COMOGLAS", manufactured by Kuraray Co., Ltd.)) and laminated. Using a laminator, the transfer sheets were heated and pressed from the transfer sheet side under conditions of a lamination roll temperature of 170°C and a conveying speed of 2 m / min to adhere to each other. The release film was peeled off from the adhered transfer sheets to obtain exterior components as evaluation members. The exterior components obtained in Examples 5 and 6 were used as they were as evaluation members.

[0179] Adhesive tape ("Cellotape (registered trademark)" manufactured by Nichiban Co., Ltd.) was applied to the evaluation member over an area of ​​2.5 cm x 2.5 cm so that it protruded about 5 cm from the edge of the evaluation member. The protruding portion of the applied adhesive tape was then pinched and the adhesive tape was peeled off in a direction at 45° to the surface of the evaluation member to check the adhesion between the layers of the transfer layer and evaluate the initial adhesion according to the following evaluation criteria. The evaluation results are shown in Table 1.

[0180] <Evaluation criteria> A: No peeling occurred between the transfer layers. B: Peeling occurred between the transfer layers.

[0181] [Weather-resistant adhesion evaluation] The above-mentioned evaluation members were subjected to the following accelerated weathering test using a metal halide lamp (MWOM) for 700 hours (a cycle of 20 hours of ultraviolet irradiation under the following irradiation conditions, followed by 4 hours of condensation under the following condensation conditions, and the cycle was repeated). The weather-resistant adhesion was then evaluated as follows. The evaluation results are shown in Table 1.

[0182] <Conditions for accelerated weathering test> (Test Equipment) Manufactured by Daipla Wintes, product name "Daipla Metal Weather" (Irradiation conditions) Illuminance: 65mW / cm 2 , Black panel temperature: 63℃, chamber humidity: 50%RH, time: 20 hours (Condensation conditions) Illuminance: 0mW / cm 2 , Humidity inside the tank: 98%RH, Time: 4 hours

[0183] Adhesive tape ("Cellotape (registered trademark)" manufactured by Nichiban Co., Ltd.) was applied to the evaluation member on which the accelerated weather resistance test was performed, over an area of ​​2.5 cm x 2.5 cm, so that it protruded about 5 cm from the edge. The protruding portion of the applied adhesive tape was then pinched and the adhesive tape was peeled off in a direction at 45° to the surface of the evaluation member to check the weather-resistant adhesion between the layers of the transfer layer, and the adhesion was evaluated according to the following evaluation criteria. The evaluation results are shown in Table 1.

[0184] <Evaluation criteria> A: No peeling occurred between the transfer layers. B: Peeling occurred between the transfer layers.

[0185] [Scratch resistance evaluation] The surface of the first protective layer of the evaluation member was subjected to a load of 300 g / cm using steel wool (Bonstar, #0000). 2 The surface condition was checked by rubbing the surface five times. The scratch resistance was evaluated according to the following evaluation criteria. The evaluation results are shown in Table 1.

[0186] <Evaluation criteria> A: Almost no change in appearance was observed. B: Significant scratches and gloss changes were observed.

[0187] [Table 1] (*The indentation hardness is the measured value for each layer of the transfer sheet in Examples 1 to 4, Comparative Example 1 and Comparative Example 2, and the measured value for each layer of the transfer product (exterior member) in Examples 5 and 6.)

[0188] As shown in Table 1, it was confirmed that the transfer sheets of Examples 1 to 4 were capable of transferring transfer layers having excellent scratch resistance and good weather-resistant adhesion of the first and second protective layers. Similarly, it was confirmed that the exterior members of Examples 5 and 6 provided good weather-resistant adhesion of the first and second protective layers and excellent scratch resistance. On the other hand, it was confirmed that the transfer sheet of Comparative Example 1 had poor initial adhesion and weather-resistant adhesion because the indentation hardness of the second layer was too high, and the transfer sheet of Comparative Example 2 had poor scratch resistance because the indentation hardness of the first layer was too low.

[0189] Thus, in the present disclosure, for example, the following inventions are provided:

[0190] [1] A transfer sheet used in the manufacture of an exterior member, The transfer sheet has a release film and a transfer layer disposed on one surface of the release film, The transfer layer has a first protective layer and a second protective layer in this order from the release film side in a thickness direction, the first protective layer contains a cured product of a first curable resin composition and a weather resistance agent; the second protective layer contains a cured product of a second curable resin composition and a weather resistance agent, the cured product of the first curable resin composition and the cured product of the second curable resin composition each contain a (meth)acrylic component and a urethane component, When a cross-sectional sample piece of the transfer sheet is prepared using a resin embedding method and a microtome, the indentation hardness of the first protective layer in a cross section is 150 MPa or more and 300 MPa or less; A transfer sheet, wherein the indentation hardness of the cross section of the second protective layer is 2 MPa or more and 50 MPa or less.

[0191] [2] The transfer sheet according to [1], wherein the first curable resin composition is an ionizing radiation curable resin composition.

[0192] [3] The transfer sheet according to [1] or [2], wherein the first curable resin composition is an electron beam curable resin composition.

[0193] [4] The transfer sheet according to any one of [1] to [3], wherein the first curable resin composition contains a urethane (meth)acrylate.

[0194] [5] The transfer sheet according to any one of [1] to [4], wherein the second curable resin composition is a thermosetting resin composition.

[0195] [6] The transfer sheet according to any one of [1] to [5], wherein the second curable resin composition contains a urethane (meth)acrylic resin.

[0196] [7] The transfer sheet according to any one of [1] to [6], wherein the second curable resin composition is a thermosetting resin composition containing a polycarbonate-based urethane (meth)acrylic copolymer.

[0197] [8] The transfer sheet according to any one of [1] to [7], wherein the first protective layer contains at least one of an ultraviolet absorber and a light stabilizer as the weather resistance agent.

[0198] [9] The transfer sheet according to any one of [1] to [8], wherein the first protective layer contains a triazine-based ultraviolet absorber as the weather resistance agent.

[0199]

[10] The transfer sheet according to any one of [1] to [9], wherein the second protective layer contains at least one of an ultraviolet absorber and a light stabilizer as the weather resistance agent.

[0200]

[11] The transfer sheet according to any one of [1] to

[10] , wherein the second protective layer contains a triazine-based ultraviolet absorber as the weather resistance agent.

[0201]

[12] The transfer sheet according to any one of [1] to

[11] , further comprising an adhesive layer on the surface of the second protective layer opposite to the first protective layer.

[0202]

[13] The transfer sheet according to

[12] , wherein the adhesive layer has a colorant.

[0203]

[14] The transfer sheet according to

[12] or

[13] , wherein the indentation hardness of the cross section of the adhesive layer is 100 MPa or more and 300 MPa or less.

[0204]

[15] A transfer sheet described in any of [1] to

[14] , having a design layer on the side of the second protective layer opposite the first protective layer.

[0205]

[16] The transfer sheet described in

[15] , having an adhesive layer on the side of the design layer opposite the second protective layer.

[0206]

[17] A method for producing a transfer sheet according to any one of [1] to

[16] , a first protective layer forming step of applying a first composition containing the first curable resin composition and the weather resistance agent to a surface of the release film and curing the composition to form the first protective layer; a second protective layer forming step of applying a second composition containing the second curable resin composition and the weather resistance agent to a surface of the first protective layer opposite to the release film, and curing the composition to form the second protective layer; The method for producing a transfer sheet comprising the steps of:

[0207]

[18] A preparation step of preparing a transfer sheet according to any one of [1] to

[16] ; a bonding step of placing the surface of the transfer sheet on the second protective layer side against a substrate and bonding the two together; The method for manufacturing an exterior member comprising the steps of:

[0208]

[19] A first protective layer, a second protective layer, an adhesive layer, and a substrate, in this order in a thickness direction, the first protective layer contains a cured product of a first curable resin composition and a weather resistance agent; the second protective layer contains a cured product of a second curable resin composition and a weather resistance agent, the cured product of the first curable resin composition and the cured product of the second curable resin composition each contain a (meth)acrylic component and a urethane component, When a cross-sectional sample piece of the transfer sheet is prepared using a resin embedding method and a microtome, the indentation hardness of the first protective layer in a cross section is 150 MPa or more and 300 MPa or less; The second protective layer has an indentation hardness of 2 MPa or more and 50 MPa or less in a cross section of the exterior member.

[0209]

[20] The exterior member according to

[19] , wherein the substrate is an acrylic plate, a polycarbonate plate, a non-flammable plate, a metal plate, a polyvinyl chloride plate, a melamine plate, or a carbon fiber reinforced plastic plate. [Explanation of symbols]

[0210] 1 ... Release film 2 … 1st protective layer 3…Second protective layer 4 … Adhesive layer 5 … Design layer 10 ... Transfer sheet 20 … Base 100 … Exterior materials

Claims

1. A transfer sheet used in the manufacture of an exterior member, The transfer sheet has a release film and a transfer layer disposed on one surface of the release film, The transfer layer has a first protective layer and a second protective layer in this order from the release film side in a thickness direction, the first protective layer contains a cured product of a first curable resin composition and a weather resistance agent, the second protective layer contains a cured product of a second curable resin composition and a weather resistance agent, The cured product of the first curable resin composition and the cured product of the second curable resin composition each contain a (meth)acrylic component and a urethane component, When a cross-sectional sample piece of the transfer sheet is prepared using a resin embedding method and a microtome, The indentation hardness of the first protective layer in a cross section is 150 MPa or more and 300 MPa or less, A transfer sheet, wherein the indentation hardness of the cross section of the second protective layer is 2 MPa or more and 50 MPa or less.

2. The transfer sheet according to claim 1 , wherein the first curable resin composition is an ionizing radiation curable resin composition.

3. The transfer sheet according to claim 1 , wherein the first curable resin composition is an electron beam curable resin composition.

4. The transfer sheet according to claim 1 , wherein the first curable resin composition contains a urethane (meth)acrylate.

5. The transfer sheet according to claim 1 , wherein the second curable resin composition is a thermosetting resin composition.

6. The transfer sheet according to claim 1 , wherein the second curable resin composition contains a urethane (meth)acrylic resin.

7. The transfer sheet according to claim 1 , wherein the second curable resin composition is a thermosetting resin composition containing a polycarbonate-based urethane (meth)acrylic copolymer.

8. The transfer sheet according to claim 1 , wherein the first protective layer contains at least one of an ultraviolet absorbing agent and a light stabilizer as the weather resistance agent.

9. The transfer sheet according to claim 1 , wherein the first protective layer contains a triazine-based ultraviolet absorbing agent as the weather resistance agent.

10. The transfer sheet according to claim 1 , wherein the second protective layer contains at least one of an ultraviolet absorbing agent and a light stabilizer as the weather resistance agent.

11. The transfer sheet according to claim 1 , wherein the second protective layer contains a triazine-based ultraviolet absorbing agent as the weather resistance agent.

12. The transfer sheet according to claim 1 , further comprising an adhesive layer on a surface of the second protective layer opposite to the first protective layer.

13. The transfer sheet of claim 12 , wherein the adhesive layer comprises a colorant.

14. The transfer sheet according to claim 12 , wherein the adhesive layer has an indentation hardness in a cross section of 100 MPa or more and 300 MPa or less.

15. The transfer sheet according to claim 1 , further comprising a design layer on a surface of the second protective layer opposite to the first protective layer.

16. The transfer sheet according to claim 15 , further comprising an adhesive layer on the surface of the design layer opposite the second protective layer.

17. A method for producing a transfer sheet according to any one of claims 1 to 16, comprising the steps of: a first protective layer forming step of applying a first composition containing the first curable resin composition and the weather resistance agent to a surface of the release film and curing the composition to form the first protective layer; a second protective layer forming step of applying a second composition containing the second curable resin composition and the weather resistance agent to a surface of the first protective layer opposite to the release film, and curing the composition to form the second protective layer; The method for producing a transfer sheet comprising the steps of:

18. A preparation step of preparing a transfer sheet according to any one of claims 1 to 16; a bonding step of placing the second protective layer side of the transfer sheet against a substrate and bonding the two together; The method for producing an exterior member comprising the steps of:

19. An exterior member having a first protective layer, a second protective layer, an adhesive layer, and a base in this order in a thickness direction, the first protective layer contains a cured product of a first curable resin composition and a weather resistance agent, the second protective layer contains a cured product of a second curable resin composition and a weather resistance agent, The cured product of the first curable resin composition and the cured product of the second curable resin composition each contain a (meth)acrylic component and a urethane component, When a cross-sectional sample piece of the exterior member is prepared using a resin embedding method and a microtome, The indentation hardness of the first protective layer in a cross section is 150 MPa or more and 300 MPa or less, The indentation hardness of the second protective layer in a cross section is 2 MPa or more and 50 MPa or less.

20. 20. The exterior member according to claim 19, wherein the substrate is an acrylic plate, a polycarbonate plate, a non-combustible plate, a metal plate, a polyvinyl chloride plate, a melamine plate, or a carbon fiber reinforced plastic plate.

Citation Information

Patent Citations

  • Three-dimensionally molded decorative film, method for manufacturing the film, decorative molding using the film, and method for manufacturing the molding

    JP2011189579A

  • Method for producing transfer sheet

    JP2016068007A

  • Transfer sheet

    JP2016068362A

  • Design transfer sheet, and decoration film and manufacturing method of decoration film

    JP2016120643A

  • Three-dimensional molding transfer film and method for manufacturing resin molding

    JP2018140632A